Job Satisfaction, Affective Commitment, and Turnover Intentions among Front Desk Staff: Evidence from Pakistan - Mehmood, Nasir; Ungku Ahmad, Ungku Norulkamar Bt.; Irum, Sobia; Ashfaq, Muhammad (International Review of Management and Marketing, 2016)
Understanding attitudes and behaviors at workplace develop organizational knowledge and capabilities to increase quality of services and help in retaining competent and skillful employees. The present study aims to investigate the relationship between job satisfaction, affective commitment, and turnover intentions among front desk staff working as customer service representatives in Pakistani banks. Data was collected through questionnaire from 106 front desk customer representatives in 5 different banks located in Rawalpindi district of northern Punjab, Pakistan. Correlation and regression analysis concluded that both, job satisfaction and affective commitment, were significantly related to the turnover intentions with negative associations. Based on the conclusions of this study, the implications for future studies are discussed. Keywords: Job Satisfaction, Affective Commitment, Turnover Intentions, Front Desk JEL Classifications: J28, J63